Individual response to transcranial direct current stimulation as a function of working memory capacity and electrode montage - Menze, Inga; Mueller, Notger G.; Zaehle, Tino; Schmicker, Marlen (Frontiers in Human Neuroscience, 2023)
Introduction: Attempts to improve cognitive abilities via transcranial direct current stimulation (tDCS) have led to ambiguous results, likely due to the method’s susceptibility to methodological and inter-individual factors. Conventional tDCS, i.e. using an active electrode over brain areas associated with the targeted cognitive function and a supposedly passive reference, neglects stimulation effects on entire neural networks. Methods: We investigated the advantage of frontoparietal network stimulation (right prefrontal anode, left posterior parietal cathode) against conventional and sham tDCS in modulating working memory (WM) capacity-dependent transfer effects of a single-session distractor inhibition (DIIN) training. Since previous results did not clarify whether electrode montage drives this individual transfer, we here compared conventional to frontoparietal and sham tDCS and reanalyzed data of 124 young, healthy participants in a more robust way using linear mixed effect modeling. Results: The interaction of electrode montage and WM capacity resulted in systematic differences in transfer effects. While higher performance gains were observed with increasing WM capacity in the frontoparietal stimulation group, low WM capacity individuals benefitted more in the sham condition. The conventional stimulation group showed performance gains independent of WM capacity. Discussion: Our results confirm previous findings of WM capacity dependent transfer effects on WM by a single-session DIIN training combined with tDCS (Schmicker et al., 2021) and additionally highlight the pivotal role of the specific electrode montage. WM capacity dependent differences in frontoparietal network recruitment, especially regarding the parietal involvement, are assumed to underlie this observation.